The performance of derivate FTIR spectrophotometry method compared to colorimetry for tranexamic acid tablet content determination - Ilma Nugrahani; Winni Nur Aulia (Universitas Ahmad Dahlan, 2018)
Recently, FTIR reported has been established as a direct content determination for some tablet dosage forms. In the method, infrared transmittance spectra was converted into the derivated absorbance form. In this present research, the methodâ€™s performance was investigated to quantified tranexamic acid in its tablet dosage form directly. The result then was compared to the colorimetry, which has been developed by another researcher. Correlations between the two methods were analyzed using t-test. The good linearity was shown at concentration range of 0.5 - 1.75% w/w at the wave number of NH group. Furthermore, the recovery, intra- and inter-day precision also fulfilled the validation requirement. Meanwhile, LOD and LOQ of the method were 0.0531%w/w and 0.1770%w/w. These methods were compared with colorimetry has been established before. Afterwards, the t-test proved no significant difference of content determination yielded, between these two methods. In conclusion, FTIR can be used for quantify the content of tranexamic tablet, more accurately than colorimetry, which has been developed before. Moreover, FTIR method also has advantages such as easier, simpler, faster and cheaper than the colorimetry method.Â Â